First record in peninsular Malaysia and morphological redescription of lychnorhiza malayensis (Scyphozoa: Rhizostomeae: Lychnorhizidae) - Syazwan, Wan Mohd; Low, Liang Boon; Rizman-Idid, Mohammed (National University of Singapore, 2020)
This study presents the first record of Lychnorhiza malayensis Stiasny, 1920, in Malaysian waters since its first discovery in the Java Sea of Indonesia nearly a century ago. Better representation of the species was achieved by the collection of more specimens than previous studies. Thirteen specimens were collected from the midwestern and northeastern coasts of Peninsular Malaysia and their morphology was examined in detail. Morphological descriptions of L. malayensis from outside Malaysia and our collection in Malaysia were compared, reviewed and updated. All Lychnorhiza species were also compared and differences highlighted. Lychnorhiza malayensis can be distinguished from its congeners primarily by the presence of subumbrellar papillae, higher counts of the centripetal canal which tends to anastomose, and the distinctive colour patterns and markings of the umbrella. Intraspecific variations were observed among specimens in terms of different papillae and centripetal canal forms, inter-rhopaliar canals that extend beyond or terminating at the circular canal, various colour patterns and markings, the number of velar lappets and size (length and width) of oral arms that were also different from previous descriptions. The morphological redescription of this species will facilitate the identification of this bloom-forming species and contribute to the inventories of marine biological resources in Malaysia. © National University of Singapore.